Analysis of CSR Index, Profitability, Sales Growth and Its Effect on Financial Performance on the Indonesia Stock Exchange in 2017-2020 - Tauada Silalahi; Surbakti Karo karo; La Hanu; Jihen Ginting; Azizul Kholis; Riska Ariani (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The purpose of the research to determine the effect of corporate social responsibility disclosure on the performance of automotive companies on the Indonesia Stock Exchange (IDX) in 2017-2020, to determine the effect of profitability on the performance of automotive companies on the Indonesia Stock Exchange (IDX) in 2017-2020, to determine the effect of sales growth on the Indonesia Stock Exchange (IDX) in 2017-2020 and to determine the effect of corporate social responsibility diclosure, profitability and sales growth simultaneously on the performance of automotive companies on the Indonesia Stock Exchange (IDX) 2017-2020. The data collection techniuqe used in this study of documentation which learn the documents related data research such as the financial statements of automotive companies on the Indonesia Stock Exchange (IDX). In addition, the data analysis techniuqe used is multiple linear regression technique. The results in the study are 1) The company’s CSR index has a partial effect on the performance of automotive companies on the Indonesia Stock Exchange in 2017-2020 which is known as value Tcount > Ttable (2.172 > 1.69092), then H0 is rejected and Ha is accepted. 2) Profitability has a partial effect on the performance of automotive companies on the Indonesia Stock Exchange (IDX) in 2017-2020 which is known as value Tcount > Ttable (2.000 > 1.69092), then H0 is rejected and Ha is accepted. 3) Sales growth has a partial effect on the performance of automotive companies on the Indonesia Stock Exchange (IDX) in 2017-2020 which known a value Tcount > TTable (3.632 > 1.69092) the H0 is rejected and Ha is accepted. 4) The company’s CSR index, profitability and sales growth have a simultaneous effect on the performance of automotive companies on the Indonesia Stock Exchange (IDX) in 2017-2020 which known as value Tcount > Ttable (4.425 > 2.87) the H0 is rejected and Ha is accepted. 5) The percentage influence of the company’s CSR index, profitability and sales growth on Return On Assets is 0,593% while the remaining 40,7% is influenced by the other factors not examined.